2019
DOI: 10.1016/j.livsci.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative grazing behaviour of lactating suckler cows of contrasting genetic merit and genotype

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Highlights  Genotype had no effect on any recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…The 66 g higher calf pre-weaning ADG from Dairybeef compared to Beef genotypes is in line with results from other studies (72-110 g, McGee et al, 2005;141-205 g, Murphy et al, 2008). The 14 kg heavier calves at weaning (210-day adjusted) from Dairybeef compared to Beef genotypes is in close agreement with a recent analysis of an Irish national database (McCabe et al, 2019b) and a cow genotype evaluation (McCabe et al, 2019a), which found that calves from beef x dairy cows were ca. 18 kg heavier at weaning (240-days) than beef genotypes.…”
Section: Calf Performancesupporting
confidence: 89%
See 1 more Smart Citation
“…The 66 g higher calf pre-weaning ADG from Dairybeef compared to Beef genotypes is in line with results from other studies (72-110 g, McGee et al, 2005;141-205 g, Murphy et al, 2008). The 14 kg heavier calves at weaning (210-day adjusted) from Dairybeef compared to Beef genotypes is in close agreement with a recent analysis of an Irish national database (McCabe et al, 2019b) and a cow genotype evaluation (McCabe et al, 2019a), which found that calves from beef x dairy cows were ca. 18 kg heavier at weaning (240-days) than beef genotypes.…”
Section: Calf Performancesupporting
confidence: 89%
“…Milk is the primary source of nutrients for the newborn calf in early postnatal life and remains a significant component of the diet until weaning (McGee et al, 2005;Grings et al, 2008;Roca Fraga et al, 2018). Beef suckler cows with higher milk yield (MY) generally produce heavier calves at weaning (Arthur et al, 1997;Murphy et al, 2008a;Minchin and McGee, 2011;Vaz et al, 2016;McCabe et al, 2019a); MY can account for up to ca. 74% of the variance in calf WW (Arthur et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, validation of overall breeding objectives, in cattle at least, is not well publicized in the scientific literature (Ramsbottom et al, 2012;Newton et al, 2017;O'Sullivan et al, 2019). To our knowledge, only 1 study has evaluated the impact on phenotypic performance from selection on a maternal breeding objective in cattle and this was a relatively small controlled study undertaken in Ireland (McCabe et al, 2019). McCabe et al (2019) failed to detect a significant difference between a high genetic group (n = 41) and low genetic group (n = 41) for body weight, body condition score, milk yield, and a range of intake traits.…”
Section: Importance Of Validationmentioning
confidence: 99%
“…To our knowledge, only 1 study has evaluated the impact on phenotypic performance from selection on a maternal breeding objective in cattle and this was a relatively small controlled study undertaken in Ireland (McCabe et al, 2019). McCabe et al (2019) failed to detect a significant difference between a high genetic group (n = 41) and low genetic group (n = 41) for body weight, body condition score, milk yield, and a range of intake traits. Although the present study does demonstrate the impact of the maternal index on individual traits, financial information at a herd-level is lacking to truly validate the index.…”
Section: Importance Of Validationmentioning
confidence: 99%
See 1 more Smart Citation